A Tool For ECG Analysis as a Module of a Tele-Monitoring System - Rocha, Teresa; Paredes, Simão; Cabiddu, Ramona; Couceiro, Ricardo; Carvalho, Paulo; Henriques, Jorge (International Journal of Online and Biomedical Engineering (iJOE), 2016)
This work describes a Matlab tool originally developed in the HeartCycle European project and updated during the cardioRisk project. It addresses the analysis of the electrocardiogram (ECG) signal in the context of the management of heart failure (HF) patients. The toolbox is composed of six modules, focusing on the major clinical aspects relevant to HF diagnosis: signal delineation, detection of auricular and ventricular arrhythmias, ST segment deviation, and heart rate variability analysis. The effectiveness of the algorithms was validated using private and public datasets.